SPOR MERKEZİ ÜYELERİNİN SAĞLIK ALGISI DURUMLARI İLE DEPRESYON, ANKSİYETE VE STRES DÜZEYLERİNİN İNCELENMESİ - BİÇER, İBRAHİM (Fırat Üniveristesi, 2022)
Spor merkezlerinde fiziksel aktivite yapan bireylerin algılanan sağlık durumlarını ve ruhsal sağlık düzeylerini bilmeleri gerektiği bilinçli spor yapma ve sağlığı iyileştirme konusunda önem arz etmektedir. Bu bağlamda spor merkezi üyelerinin ve sağlık algısı durumları ve depresyon, anksiyete ve stres düzeylerinin farklı değişkenler açısından incelenmesi amaçlanmıştır. Araştırmamıza, Mardin ilinde spor merkezlerine üye olan 155 kadın, 178 erkek, toplam 333 gönüllü birey katılmıştır. Araştırma nicel (kantitatif) araştırma yöntemlerinden olan tarama (survey) modelinde bir çalışmadır. Veri toplama aracı olarak, tarafımızca geliştirilen "Kişisel Bilgi Formu" üyelerin sağlık algı durumlarını belirlenmesi için "Sağlık Algısı Ölçeği" ve depresyon, anksiyete ve stres düzeylerini incelemek için "Depresyon, Anksiyete ve Stres Ölçeği – 21" kullanılmıştır. Ölçeklerden elde edilen verilerin istatistiksel analizi, SPSS 23.0 paket programında yapılmıştır. İstatistiksel analizler yapılmadan önce yapılan normallik testlerinde, verilerin normal dağılım gösterdiği görülmüştür. Bu nedenle, verilerin analizinde parametrik testler tercih edilmiştir. İkili değişkenlerde ki farklılığı saptamak için T- testi, iki değişkenden daha fazla değişkene sahip olan verilerdeki farklılığı saptamak için ANOVA testi kullanılmıştır. İstatistiksel analizlerde anlamlılık düzeyi p<0.05 olarak kabul edilmiştir. Araştırmada elde edilen bulgularda katılımcıların "Sağlık algısı ölçeği" toplam ve alt boyut puanları incelendiğinde; medeni durum, yaş, eğitim, egzersiz yapma yılı ve egzersiz süresi değişkenlerinde anlamlı farklılıklar bulunurken cinsiyet değişkeninde anlamlı farklılık bulunmamıştır. Katılımcıların "depresyon, anksiyete ve stres ölçeği – 21" toplam ve alt boyut ölçek puanları incelendiğinde; eğitim ve egzersiz yılı değişkenlerinde anlamlı farklılıklar bulunmuş, cinsiyet, medeni durum, yaş, egzersiz süresi değişkenlerinde anlamlı farklılık bulunmamıştır. Son olarak; her iki ölçeğin alt ölçek puan ortalamaları arasındaki ilişkiye yönelik korelasyon analizi sonuçlarında "Sağlık Algısı Ölçeği" ve "Depresyon, Anksiyete ve Stres ölçeği – 21" arasında negatif yönde zayıf ilişki bulunmaktadır. Anahtar Kelimeler: Spor merkezi, sağlık algısı, depresyon, anksiyete, stres

It is important for individuals who do physical activity in sports centers to know their perceived health status and mental health level in order to do exercise consciously and to promote health. In this context, it is aimed to examine the members of the sports center and their health perception status and depression, anxiety and stress levels in terms of different variables. A total of 333 voluntary individuals (including 155 women and 178 men), who were the members of the sports centers in the Mardin province, participated in the study. The research is a study conducted in the survey model, which is one of the quantitative research methods. The "Personal Information Form" prepared by the researcher, the "Perception of Health Scale" to determine the health perception status of the members, and the "Depression, Stress Anxiety Scale - 21" to examine the depression, anxiety, and stress levels were used as data collection tools. Statistical analysis of the data obtained from the scales was performed in the SPSS 23.0 software. The normality tests performed before statistical analysis indicated that the data were normally distributed. Therefore, parametric tests were preferred in the analysis of the data. While T-test was used to detect the difference in binary variables, ANOVA test was used to detect the difference in data with more than two variables. Significance level was accepted as p<0.05 in statistical analysis. When examining "Perception of Health Scale" total and subscale scores of the participants based on the findings obtained in the study, it was found that while there were significant differences in the variables of marital status, age, education, duration of exercise (in years) and time of exercise, there was no significant difference in the gender variable. When " Depression, Stress Anxiety Scale - 21" total and subscale scores of the participants were analyzed, it was found that while there were significant differences in the variables of education and years of exercise, no significant difference was detected in the variables of gender, marital status, age, and time of exercise. Finally, the results of the correlation analysis regarding the correlation between the subscale mean scores of both scales indicated that there was a negative weak correlation between " Perception of Health Scale " and " Depression, Stress Anxiety Scale - 21". Key words: Sports center, health perception, depression, anxiety, stress
Examination of health perception status and depression, ANXİETY, and stress levels of the sports center members
Keywords: Spor